Beyond the primal addiction food, sex, gambling, internet, shopping and work - Savelle-Rocklin, Nina; Akhtar, Salman 1946 July 31- (Routledge, 2019)
Written by experienced practitioners in the fields of addiction and psychoanalysis, and illustrated by a range of moving vignettes, this groundbreaking book examines the psychological foundations of addiction in the areas of food, sex, gambling, internet usage, shopping, and work. This book not only explores the roots of addictive behavior, explaining why popular treatment options such as the 12-Step Program often fail, it also provides insights for emotional resolution and strategies for behavioral change. Beyond the Primal Addiction seeks to understand rather than pathologize addictive behaviours, now so pervasive in contemporary societies. It will be essential reading for psychoanalysts, psychotherapists, and other mental health professionals, as well as their clients